Solved

Help please, solve for X - simple algebra

Posted on 2013-12-18
7
407 Views
Last Modified: 2013-12-18
Can you help me reorder this equation?  I know it must be possible:

F = ( (X/Y)^(1/P-1) ) -1)
0
Comment
Question by:Geoff Millikan
[X]
Welcome to Experts Exchange

Add your voice to the tech community where 5M+ people just like you are talking about what matters.

  • Help others & share knowledge
  • Earn cash & points
  • Learn & ask questions
  • 4
  • 2
7 Comments
 
LVL 27

Expert Comment

by:aburr
ID: 39727693
What order do you want?

Try
let r = (1/P)-1          (not 1/(P-1)

F = (X^r)/Y^r) - 1
0
 
LVL 84

Expert Comment

by:ozo
ID: 39727694
F = ( (X/Y)^(1/P-1) ) -1
F+1 = (X/Y)^(1/P-1)
(F+1)^-(1/P-1) = (X/Y)
Y*(F+1)^-(1/P-1) = X
0
 

Author Comment

by:Geoff Millikan
ID: 39727757
ozo, your equation doesn't seem to work when I put in real numbers.  I get 18.43 on your formula but was expecting 34.

F = 2.4
X = 34
Y = 10
P = 2

2.4    = ((34/10)^(1/(2-1))-1)

10*(2.4+1)^-(1/2-1) = 18.43
0
Independent Software Vendors: We Want Your Opinion

We value your feedback.

Take our survey and automatically be enter to win anyone of the following:
Yeti Cooler, Amazon eGift Card, and Movie eGift Card!

 
LVL 84

Expert Comment

by:ozo
ID: 39727781
when you plug in
X = 34
Y = 10
P = 2
( (34/10)^(1/2-1) ) -1 = -0.4576738554533 != 34
0
 
LVL 84

Expert Comment

by:ozo
ID: 39727784
((34/10)^(1/(2-1))-1)
is different from ( (X/Y)^(1/P-1) ) -1)
0
 
LVL 84

Accepted Solution

by:
ozo earned 500 total points
ID: 39727803
(F+1)^-(1/P-1) = (X/Y)
Y*(F+1)^-(1/P-1) = X
Should have been
(F+1)^(1/P-1)^-1 = (X/Y)
Y*(F+1)^(1/P-1)^-1 = X
or if (1/P-1) was really  (1/(P-1))
(F+1)^(P-1)/1 = (X/Y)
Y*(F+1)^(P-1)/1 = X
0
 

Author Comment

by:Geoff Millikan
ID: 39728051
I get 2.4 when I cut and paste the following into Excel :  ((34/10)^(1/(2-1))-1)

But this formula works great!   Y*(F+1)^(P-1)/1 = X

For proof, I get 34 in Excel when I plug in the numbers: 10*(2.4+1)^(2-1)/1

Awesome, thanks so much!!!!!!!!!!!!!!!

Note to self:

This is the reverse CAGR formula http://www.igetit.net/newsletters/Y06_08/CalculateGrowth.aspx

F = 2.4 (CAGR, in percent, annualized)
X = 34  (Ending dollar amount)
Y = 10 (starting dollar amount)
P = 2 (period [in years])
0

Featured Post

Technology Partners: We Want Your Opinion!

We value your feedback.

Take our survey and automatically be enter to win anyone of the following:
Yeti Cooler, Amazon eGift Card, and Movie eGift Card!

Question has a verified solution.

If you are experiencing a similar issue, please ask a related question

Complex Numbers are funny things.  Many people have a basic understanding of them, some a more advanced.  The confusion usually arises when that pesky i (or j for Electrical Engineers) appears and understanding the meaning of a square root of a nega…
We are taking giant steps in technological advances in the field of wireless telephony. At just 10 years since the advent of smartphones, it is crucial to examine the benefits and disadvantages that have been report to us.
This is a video describing the growing solar energy use in Utah. This is a topic that greatly interests me and so I decided to produce a video about it.
Although Jacob Bernoulli (1654-1705) has been credited as the creator of "Binomial Distribution Table", Gottfried Leibniz (1646-1716) did his dissertation on the subject in 1666; Leibniz you may recall is the co-inventor of "Calculus" and beat Isaac…

691 members asked questions and received personalized solutions in the past 7 days.

Join the community of 500,000 technology professionals and ask your questions.

Join & Ask a Question